Development of catalytic methods to exploit sulfur dioxide in organic synthesis - Emmett, EJ (2014)
In the following thesis, new methodologies towards the synthesis of a range of sulfonyl (-SO2-) containing functional groups are documented. These methods utilise easy-to-handle sulfur dioxide surrogates, such as DABSO (vide infra), and exploit palladium catalysis as a new mechanistic protocol for the incorporation of the -SO2- unit. Chapter 1 is a literature review surveying sulfur dioxide in organic synthesis, the established uses of SO2 surrogates and the importance of the sulfonyl moiety in chemistry. Palladium-catalysed (carbonylative) cross-couplings are also broadly discussed as they provide inspiration for, and mechanistic similarities with, the proposed chemistry. Chapter 2 describes a de novo synthesis of the sulfonamide functional group; a three-component and convergent methodology coupling (hetero)aryl and alkenyl halides with sulfur dioxide (provided by easy-to-handle surrogates such as DABSO) and hydrazine nucleophiles, is documented. This is achieved through the action of a readily available palladium catalytic system and is the first example of a metal-catalysed sulfonylative cross-coupling of halide based electrophiles. Chapter 3 presents a new method of generating (hetero)aryl and alkenyl sulfones. The ability of organometallic reagents to add to sulfur dioxide (supplied via DABSO) is applied to deliver the corresponding metal sulfinate salt. This in situ derived sulfinate is coupled with an (hetero)aryl or alkenyl (pseudo)halide using palladium catalysis to form the desired sulfone. An electronically modified XantPhos-type ligand was designed for the reaction in order to suppress unwanted aryl-aryl exchange. Chapter 4 documents the generation of (hetero)aryl and alkenyl sulfinates from the corresponding halide and DABSO through a palladium-catalysed sulfination protocol, obviating the need for organometallic reagents. A mild set of conditions using IPA as both a solvent and reductant together with a low loading of palladium catalyst offers an attractive route to sulfonyl compounds thanks to the in situ derived sulfinates being converted into a broad variety of functional groups via established onwards reactivity. Chapter 5 discusses the conclusion of the research and the potential for future work. Chapter 6 presents the experimental data.